Analisis Pelaksanaan Kebijakan Free Trade Zone (FTZ) di Kawasan Kota Tanjungpinang Kepulauan Riau - Prastya, Imam Yudhi; Kustiawan, Kustiawan (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2015)
Analisis Pelaksanaan Kebijakan Free Trade Zone (FTZ) di Kawasan KotaTanjungpinang Kepulauan Riau   Kustiawan(Jurusan Ilmu Pemerintahan FISIP UMRAH) Imam Yudhi Prastya (yudhiimam@yahoo.co.id)(Jurusan Ilmu Administrasi Negara FISIP UMRAH) Abstract From the results of the study concluded that the implementation of FTZ in Tanjungpinang have not great results, there is no business or industry in those areas that have been set (Dompak -Senggarang areas). It is caused by; Legal assurance land ownership, infrastructure ; roads, ports, limited supply of electricity , synergy between the board of zone, local government and principals of some program activity is inhibited and can not be done, especially in matters relating to budget authority and the licensing process, the board of zone of Tanjungpinang unclear.